Insecticidal activities of fi ve plant derived chemicals on Thrips tabaci Lindeman - Najmizadeh, Hakimeh; Ahmadi, Kamal; salari, Asieh (Pharmacognosy Communications)
Background: Natural compounds originating from plants might be potential alternative pesticide that are not persistent in the environment and are safe to non-target organisms and for use in sustainable agriculture. Methods: Ethanolic extracts (30 μl/mL) of Melia zedarach L. (Fruits), Peganum harmala L. (seeds), Calendula offi cinalis L. (seeds), Ferula assafoetida L. (resin) and Cercis siliquastrum L. (seeds) were applied against 1–2 and 5–6 days of Thrips tabaci Lindeman. All the experiments were conducted by spray test bioassay. Ethanol (95%) was used as a control treatment. Results: All the plant derived chemicals were highly toxic against the pre-imago thrips. The mortality percentages of the pest (1–2day old) after 72 hours were more than 66.0% in each of the plant extracts. The highest insecticidal activity against the above-mentioned pre-imago thrips was recorded for the F. assafoetida treatment (96.7%). Insecticidal activity was more than 85% in the ethanolic extract M. azedarach and P. harmala treatments. Moreover, the mortality percentage of the thrips (5–6-day old) after 72 hours was more than 80.6% in the ethanolic extract of F. assafoetida treatment. Conclusions: The plant derived chemicals tested in this study may be useful as a insecticide in T. tabaci management programs, although their safety towards humans needs verifi cation.
Keywords: Melia azedarach; Peganum harmala; Calendula offi cinalis; Ferula assafoetida; Cercis siliquastrum; Mortality percentage; Thrips tabaci